Artikel Review: Aplikasi Inokulum Fungi Trichoderma spp. Untuk Pertumbuhan dan Penekan Fitopatogen - Ega F.S. Bina; Bambang Irawan; Wawan A. Setiawan; Christina N. Ekowati (Jurusan Biologi FMIPA Universitas Cenderawasih, 2022)
The growth of a plant is influenced by the availability of nutrients. To meet these nutritional needs, chemical fertilizers are still widely used. In addition to nutritional needs, the growth of a plant is also influenced by pathogenic microorganisms that cause disease. The emergence of diseases in plants causes chemical pesticides to be increasingly used. The continuous use of chemical fertilizers and chemical pesticides can make living organisms susceptible to high toxicity of chemical compounds. In addition, the impact has an impact on improper management of agricultural waste as well as polluting the environment when it has been burned or discharged into water bodies. One alternative to overcome these problems is the application of biological control using Trichoderma spp. Trichoderma spp inoculum application can significantly regulate the rate of plant growth and suppress the growth of plant pathogenic microorganisms. Trichoderma spp. including plant growth promoting microbes that have the ability to colonize plant roots so as to provide benefits to their host, modulate phytohormonal production, increase soil nutrient availability, stimulate plant growth and tolerance to biotic and abiotic stresses, and resistance to pathogens. Inoculum of Trichoderma spp. can be applied to plants through seeds, leaves, roots of seedlings, and soil. Based on literature review, it is known that the application of Trichoderma spp. inoculum showed a significant effect on plant growth and suppress the growth of pathogenic microorganisms.Key words: Trichoderma spp.; inoculum; fungi; biofertilizer; biofungicide.